Trends in Ubiquitous Learning Research: A Micro Study of Selected Publications from 2000 to 2015 - Coto-Chotto, Mayela (2017)
This article analyzes trends in ubiquitous learning research during the period 2000-2015. We searched for articles in English and Spanish that specifically addressed the topics of "ubiquitous learning" or "aprendizaje ubicuo". The selected papers were analyzed in the following categories: target population, subject area, type of contribution, country, publication media and type of paper. The results indicate that most of the initiatives are directed towards primary education; they do not address a specific subject area; and they contribute to the ubiquitous learning domain with the development of technology platforms. The country that has a dominant presence is Taiwan; the more prevalent publication journals are Computers and Education and Journal of Educational Technology & Society; and the kind of articles that are published have an orientation towards practical applications. The results serve as reference for educators and researchers who wish to contribute to this domain of knowledge, and for government authorities and educational institutions planning to promote and facilitate ubiquitous learning.